Improvement of dynamics of electric drive with phase synchronization, built on the basis of pulsed frequency-phase discriminator with extended functional possibilities - A. V. Bubnov; A. N. Chetverik (Омский научный вестник)
The electric drive with phase synchronization, widely used in thermal imaging and laser scanning systems due to the high dynamic characteristics in a wide range of adjustment of the angular velocity. The aim of the article is development of management method by an electromechanic with phase synchronization, realized on the basis of impulsive frequencyphase discriminator with the extended linear zone in the mode of phase comparison of entrance impulsive sequences. The method for controlling the electric drive with phase synchronization with the implementation of a control system based on a pulse frequency-phase discriminator with enhanced functionality has been improved. Schematic implementations of the logical comparison device with the extended linear zone of the IPFD in the phase comparison mode, which allow improving the dynamics of the electric drive in synchronization mode, are proposed.